Functional lipid characteristics of Turkish Tombul hazelnut (Corylus avellana L.) - Alasalvar, Cesarettin (2006)
The quality of crude oil extracted from Tombul (Round) hazelnut, grown in the Giresun province of Turkey, was evaluated for its fatty acid, triacylglycerol (TAG), tocol, and phytosterol compositions. Oleic acid contributed 82.78% to the total fatty acids, followed by linoleic, palmitic, and stearic acids. Among 12 TAGs separated, 11 were identified (including one unknown): LLL, OLL, PLL, OOL, POL, PPL, OOO, POO, PPO, SOO, and PSO (where P, palmitoyl; S, stearoyl; O, oleoyl; and L, linoleoyl). The main components were OOO (71.31%), OOL (12.26%), and POO (9.45%), reflecting the high content of oleic acid present in hazelnut oil. Seven tocol isoforms (four tocopherols and three tocotrienols) and eight phytosterols as well as cholesterol were positively identified and quantified; among these, R-tocopherol (40.40 mg/100 g) and -sitosterol (134.05 mg/100 g) were predominant in hazelnut oil and contributed 78.74 and 81.28% to the total tocols and phytosterols present, respectively. Tocotrienols were detected in small amounts (1.02% to the total tocols). The crude hazelnut oil extracted from Turkish Tombul hazelnut, thus, serves as a good source of nutrients, bioactives, and health-promoting components.